Practical Analysis Antibiotics Use for Covid 19 Patients - Puri Safitri Hanum; Ni Made Eravikania Putri Darmawan; Didik Hasmono (Budapest International Research and Critics University, 2021)
To evaluate the use of antibiotics and their effectiveness in COVID-19 patients including PCR, body temperature, SaO2, chest X-ray, respiratory rate, leukocytes, CRP, and LOS of COVID-19 patients at Bhayangkara HS Samsoeri Hospital Mertojoso Surabaya. This study is an observational study with a retrospective method in the period June 2020 to February 2021. Data were collected from Medical Records of COVID-19 patients who achieved antibiotic therapy, with standard therapy: antiviral (mild to moderate: Favipiravir-Ritonavir and severe: Remdesivir), antibiotics, vitamins, anticoagulants, corticosteroids, symptomatic and concomitant therapy. The study showed that 37% (25 patients) were female and 67% (41 patients) were male with the highest age range between 30-39 years. Most of the patients were hospitalized for 10-14 days and the longest hospitalization period was 40-44 days. In this study patients with mild cases were the most cases with a total of 36 patients (54%). The results of the analysis based on the 2020 Third Edition of the 2020 COVID-19 Handling Guidelines, the Bhayangkara Hospital Antibiogram data, clinical conditions and laboratory tests occurred in 66 patients (100%). Rational use of antibiotics in accordance with the COVID-19 Management Guidelines 3rd Edition and data from Bhayangkara Hospital antibiogram of 100% and antibiotics can help the healing process of COVID-19 patients proven by negative PCR results (91%), increased body temperature (100%), SaO2 (100%), chest x-ray (45%), respiratory rate (92%), leukocytes (77%), CRP (41%), and LOS.